Two interesting sentences regarding to the possibility of patenting genes and embryos - Cárdenas Krenz, Ronald (2013)
The article discusses two important sentences given in Europe and the United States in 2011 and 2013, respectively, declaring the impossibility of patenting genes and embryos.